2021
DOI: 10.21149/12501
|View full text |Cite
|
Sign up to set email alerts
|

Impacto del aislamiento por la pandemia de Covid-19 en hábitos de la vida diaria en población mexicana

Abstract: No disponible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
3
0
3
Order By: Relevance
“…Exploring the effects of confinement on health habits such as eating disorders or physical activity is quite relevant in the context of a population such as the inhabitants of Mexico City, and given that in much of the Mexican population, there is a high level of food insecurity, a large problem of overweight and obesity, sedentary lifestyle, and high rates of the population with metabolic comorbidities (36-38). The preliminary reports of the study "PSY-COVID-19" (39), with more than 7,000 responses from Mexicans surveyed through a Google form, revealed that around half of the participants reduced their physical activity (more often men than women) and neglect their nutrition (more often women than men) during the first months of confinement (39). In our case, 38.31% of men and 42.78% of women did not perform any physical activity; however, 45.50% of men and 44.64% of women did take care of their nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the effects of confinement on health habits such as eating disorders or physical activity is quite relevant in the context of a population such as the inhabitants of Mexico City, and given that in much of the Mexican population, there is a high level of food insecurity, a large problem of overweight and obesity, sedentary lifestyle, and high rates of the population with metabolic comorbidities (36-38). The preliminary reports of the study "PSY-COVID-19" (39), with more than 7,000 responses from Mexicans surveyed through a Google form, revealed that around half of the participants reduced their physical activity (more often men than women) and neglect their nutrition (more often women than men) during the first months of confinement (39). In our case, 38.31% of men and 42.78% of women did not perform any physical activity; however, 45.50% of men and 44.64% of women did take care of their nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Según la evidencia disponible, en México existen pocos estudios (Arce-García, Mendoza-Ayala, Álvarez-Aguirre, Reyes-Rocha y Sánchez-Perales, 2018; Escobar-Castellanos et al, 2019) que analizan el estilo de vida y sus consecuencias en la salud, así como el impacto de la pandemia en los hábitos de la población mexicana (Aguilar-Díaz, Ramírez-Trujillo, Villanueva-Vilchis y De la Fuente-Hernández, 2021;Rico-Gallegos et al, 2020), lo cual representa una oportunidad para la generación de conocimiento sobre el tema, y expone la necesidad de explorar más sobre la problemática, para llegar a su comprensión global y encontrar alternativas que permitan alcanzar estilos de vida cada vez más saludables en la población y en las futuras generaciones.…”
Section: Impacto De La Pandemia En Los Estilos De Vidaunclassified
“…Los autores Carmen Díaz et al, publicaron el trabajo sobre "Impacto del aislamiento por la pandemia de la COVID -19 en hábitos de la vida diaria en población mexicana" y reportaron cambios negativos en la alimentación, más las mujeres que los hombres. Más de 45% aumentó la frecuencia y cantidad de alimentos ingeridos, 32.2% fumó más, 17.6% ingirió más alcohol y la actividad física disminuyó en 36% (13).…”
Section: Marco De Referenciaunclassified